2021
DOI: 10.1186/s12968-021-00757-w
|View full text |Cite
|
Sign up to set email alerts
|

Regional adiposity, cardiorespiratory fitness, and left ventricular strain: an analysis from the Dallas Heart Study

Abstract: Background Low cardiorespiratory fitness (CRF), high body mass index, and excess visceral adiposity are each associated with impairment in left ventricular (LV) peak circumferential strain (Ecc), an intermediate phenotype that precedes the development of clinical heart failure (HF). However, the association of regional fat distribution and CRF with Ecc independent of each other and other potential confounders is not known. Methods Participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our result demonstrated that central fat distribution (visceral and android fat) had a negative association, while peripheral fat distribution (gynoid fat) had a positive association on LV function. Prior study have also revealed that VAT is independently associated with impairment of LV strain, while lower-body fat is not associated with it [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result demonstrated that central fat distribution (visceral and android fat) had a negative association, while peripheral fat distribution (gynoid fat) had a positive association on LV function. Prior study have also revealed that VAT is independently associated with impairment of LV strain, while lower-body fat is not associated with it [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dual X-ray absorptiometry (DXA) is widely used for assess body fat distribution. Several studies have reported the associations of LV remodeling or peak circumferential strain with DXA-derived fat distribution parameters, such as total body fat, lean mass, lower body fat, and visceral or subcutaneous fat [ 15 17 ]. A recent study revealed the different effects of central and peripheral fat distributions on right ventricular function [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high-throughput cell-free test was developed as an HDL function surrogate based on lipid peroxidation of HDL, and it was reported to be consistent with CV events risk [ 12 ]. The Dallas Heart Study [ 13 ] and other studies with big groups of people evaluated CEC as a measure of HDL function using cell techniques, such as fluorescent reagents (e.g., bodipy—boron dipyrromethene difluoride) and radioactively labeled cholesterol. The highest quartile indicated a 67% decrease in cardiovascular risk compared with the lowest quartile of CEC.…”
Section: Hdl-c Levels Vs Hdl Functionmentioning
confidence: 99%
“…EAT is anatomically and functionally continuous with the myocardium, whereas PAT is located between the visceral and parietal pericardium ( Rafeh et al, 2020 ; Despres et al, 2021 ). The accumulation of excess VAT and PAT plays independent and crucial roles in the pathophysiology of cardiac structural and functional changes ( Kenchaiah et al, 2021 ; Kim et al, 2021 ; Kondamudi et al, 2021 ; Sorimachi et al, 2021 ).…”
Section: Primary Mechanisms Of Hiit In Cardiac Fitness Improvements I...mentioning
confidence: 99%